Pengembangan Sistem Peningkatan Notifikasi Real-Time Pada Aplikasi Estimate Time Arrival (Eta) Trans Koetaradja Dinas Perhubungan Aceh - Alfina; Sulfi, Arief Raisal; Ismail (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study aims to develop a real-time notification system for the Estimated Time of Arrival (ETA) Trans Koetaradja application managed by the Aceh Department of Transportation, focusing on improving user responsiveness and reliability. Observations revealed that the existing notification feature was ineffective—it only functioned when the application was open, failed to operate in the background, and did not personalize information based on user location. A qualitative descriptive approach was applied using the User Centered Design (UCD) method to create a system that adapts to user needs through stages of requirement analysis, prototype design, and user evaluation. Based on questionnaires distributed to thirty respondents, 87% expected automatic notifications when the bus approached their stop, while 73% wanted customizable alerts based on routes and preferred schedules. The prototype, developed with Adobe XD, includes location-based notifications, adjustable reminders, and clearer visual indicators. Evaluation using the System Usability Scale (SUS) resulted in an average score of 81.2, categorized as Excellent, with 90% of users expressing satisfaction with the improved system. The findings demonstrate that applying UCD effectively enhances notification speed, accuracy, and relevance, while strengthening public trust in digital-based transportation services in Banda Aceh.